Mendorong Inovasi dan Jiwa Kewirausahaan Generasi Muda Di Era Digital - Kholifatul Fatwaa; Siti Haniah Fatimah; Tri Wulandari (Jurnal Ekonomi dan Bisnis Digital, 2026)
The rapid development of digital technology has created significant opportunities for young people to engage in entrepreneurship; however, many vocational high school students still lack an adequate entrepreneurial mindset. This Community Service Program aims to develop a growth mindset and entrepreneurial spirit among Grade 10 students of the Marketing Department at SMK Puspita Bangsa. The program was implemented through an educative and participatory approach, including material presentations, interactive discussions, and the introduction of inspirational entrepreneurs in the digital era. The materials focused on growth mindset concepts, entrepreneurial characteristics, productive use of digital technology, and resilience in facing challenges. The results indicate increased students’ understanding, motivation, and awareness of digital entrepreneurship opportunities from an early stage.